Towards gender equality: A review of evidence on social safety nets in Africa - Peterman, Amber; Kumar, Neha; Pereira, Audrey; Gilligan, Daniel O. (International Food Policy Research Institute, 2019)
Over the last decade, social safety nets (SSNs) have rapidly expanded in Africa, becoming a core strategy for addressing poverty, responding to shocks, increasing productivity and investing in human capital. Poverty, vulnerability and well-being have inherent gender dimensions, yet only recently has gender equality been considered as a potential program objective. This study reviews the evidence on the impact of SSNs on women’s wellbeing in Africa, while contributing to an understanding of how SSNs affect gender equality. We first motivate and take stock of how gender shapes the design and effectiveness of SSNs in Africa. We then summarize evidence from rigorous impact evaluations of SSNs on women’s wellbeing across five key domains from 38 studies on 28 SSN programs across 17 countries. We find substantial evidence that, in many instances, SSNs decrease intimate partner violence and increase psychological wellbeing for women, as well as moderate evidence that SSNs increase dietary diversity and economic standing. We find minimal evidence that SSNs improve women’s food security and nutrition; however, few studies measure these outcomes for women. Finally, a substantial body of evidence reports on the impact of SSNs on women’s empowerment and intra-household bargaining power, however, with weak and mixed results. Our findings are generally promising, since most SSNs are not designed specifically to increase women’s wellbeing. However, the results show that household-level impacts do not automatically imply individual women benefit, and further that conclusions from global evidence reviews do not necessarily apply in Africa. There is little research that rigorously identifies the design features and impact pathways from SSNs to gender equality and women’s wellbeing, suggesting a priority for future research.